Application of Ultraviolet Light in Dental Identification of Avalanche Victims - Agrawal, Nitin Kumar; Dahal, Samarika; Wasti, Harihar; Soon, Alistair (Journal of Nepal Health Research Council, 2017)
In any disaster, it becomes important to identify the deceased for ethical, social and legal causes.Out of the numerous methods of identification, dental comparison is considered to be one of the scientific methods in a Disaster Victim Identification process. The two victims of avalanche in Nepal were identified using dental comparison. The two bodies brought for examination were unidentifiable visually. To aid identification of tooth coloured restorations, ultraviolet light was used. The ultraviolet light made the tooth coloured restorations appear distinct from the adjacent tooth structure in one of the cases. This helped in post-mortem charting of dental examination with greater accuracy. When the ante-mortem dental records and the post-mortem dental findings were compared, positive identification was made for both the cases. The bodies were then handed over to their respective kin. These cases highlighted the importance of ultraviolet light in post-mortem dental examination and the significance of forensic dentistry in identification process.